2015
DOI: 10.1590/s0100-736x2015000500003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular survey of porcine teschovirus, porcine sapelovirus, and enterovirus G in captive wild boars (Sus scrofa scrofa) of Paraná state, Brazil

Abstract: RESUMO.-[Estudo molecular de teschovírus suíno, sapelovírus suíno e enterovírus G em javalis (Sus scrofa scrofa) de cativeiro no Paraná.] Teschovírus suíno (PTV), sapelovírus suíno (PSV) e enterovírus G (EV-G) são agentes infecciosos específicos da espécie suína que estão endemicamente disseminados em todo o mundo. O objetivo deste estudo foi investigar a infecção natural por estes picornavírus entéricos suínos em javalis (Sus scrofa scrofa) do estado do Paraná, Brasil e avaliar pecaris (Pecari tajacu e Tayass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Although PSV is ubiquitous and is associated with a variety of clinical symptoms in domestic and wild pigs, PSVs infecting swine are often ignored for their subclinical manifestations and co-infections with other pathogens [ 9 , 10 ]. Therefore, it is necessary to develop a convenient, sensitive and accurate detection method for PSV early warning and rapid diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although PSV is ubiquitous and is associated with a variety of clinical symptoms in domestic and wild pigs, PSVs infecting swine are often ignored for their subclinical manifestations and co-infections with other pathogens [ 9 , 10 ]. Therefore, it is necessary to develop a convenient, sensitive and accurate detection method for PSV early warning and rapid diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The results in this study are in agreement with previous porcine enteric picornavirus-based studies conducted in Brazil that revealed that TV-A was detected most frequently (45%, 18/40), followed by EV-G (40%, 16/40); SV-A was the least (17.5%, 7/40) common virus present in the fecal samples evaluated and was not detected in the feces of suckling piglets [15]. In another Brazilian study in which fecal samples from wild boars were evaluated, the results revealed that EV-G was most frequently (11/22, 50%) detected, followed by TV-A (10/22, 45.5%) and SV-A (4/22, 18.2%) [16].…”
Section: Responsible Editor: Fernando Spilkimentioning
confidence: 89%
“…The nucleic acids were extracted from fecal suspensions using a combination of phenol/chloroform/isoamyl alcohol (25:24:1) and silica/guanidinium isothiocyanate extraction methods [18,19]. Fecal samples BRA/UEL1/11, BRA/ UEL-WB20/13, and BRA/UEL4/13, previously known as positive for TV-A, SV-A, and EV-G [15,16] and an aliquot of ultrapure autoclaved water were included as positive and negative controls, respectively, during the nucleic acid extraction and the following procedures. The presence of TV-A, SV-A, and EV-G ssRNA in fecal samples was determined using previously described RT-nested PCR assays [16,17].…”
Section: Responsible Editor: Fernando Spilkimentioning
confidence: 99%
See 1 more Smart Citation
“…The countries that confirmed the presence of PSVs are shown in Fig. 14.2 (Forman et al 1982;La Rosa et al 2006;Buitrago et al 2010;Lan et al 2011;Shan et al 2011;Cano-Gomez et al 2013;Schock et al 2014;Donin et al 2014Donin et al , 2015. The most immunodominant protein VP1 in the capsid of PSVs is used for estimating the divergence among the strains.…”
Section: Geographic Distribution and Strain Variabilitymentioning
confidence: 99%